An English Academic Writing Course for Secondary Schools - A Pilot Study - Arnbjörnsdóttir, Birna; Prinz, Patricia (Menntavísindasvið Háskóla Íslands, 2016)
Recent studies suggest that there is a dissonance between the focus of EFL instruction in Icelandic secondary schools and the English needs of Icelandic students at university and in the work force (Anna Jeeves, 2013; Birna Arnbjörnsdóttir, 2011; Birna Arnbjörnsdóttir & Hafdís Ingvarsdóttir, 2010; Robert Berman, 2011). The results of these studies indicate an emphasis on basic conversational (often receptive) English skills, that secondary students attain outside of the classroom, at the expense of formal academic literacy skills needed for study at the tertiary level. Recently, the Department of English at the University of Iceland developed a series of special writing courses designed to enhance students’ English academic proficiency. One of the courses was deemed appropriate for secondary school. This article describes the adaptation and implementation of one of the university courses at the secondary level. The article outlines the art and architecture of the course, that focuses on awareness of different genres, demonstrations and scaffolded practice prior to production of academic text. The article presents some qualitative outcomes from a pilot iteration of the project. The findings suggest that students find writing less interesting than other activities such as watching movies, but that they recognize the future value of instruction aimed at enhancing their academic English proficiency. Nýlegar rannsóknir á stöðu enskukennslu og enskunáms í framhaldsskólum benda til þess að meiri áherslu vanti á akademíska ensku, bæði ritaða og talaða (Anna Jeeves, 2013; Birna Arnbjörnsdóttir, 2011; Birna Arnbjörnsdóttir og Hafdís Ingvarsdóttir, 2010; Robert Berman, 2011). Ósamræmi virðist vera milli áherslna í kennslu á framhaldsskólastigi og þarfa nemenda í háskólastarfi eða atvinnulífinu. Nemendur í framhaldsskólum almennt virðast hafa ánægju af enskunámi en kvarta yfir því að enskunámið bæti litlu við þá ensku sem þau læra utan skólans sem er almennt talmál sem þau heyra oftar en þau beita því í samskiptum og ...